PERAN TEKNIK FISIKA DALAM PERKEMBANGAN TEKNOLOGI - Happy Alyzhya Haay; Agnes Julia Kopeuw; Sakka Irawan; Rosdiana Yoku (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Engineering Physics is a discipline that integrates concepts from physics, mathematics, and engineering to provide solutions to various technological challenges. The community service activity aimed to discuss the role of Engineering Physics in technological development with students at SMKS Lachairoi Kotaraja. Engineering Physics contributes to the development of innovative technologies such as renewable energy, environmental sensors, medical devices, and industrial automation. The methods used in this community service activity included expository presentations (verbal delivery of material) and demonstrations with teaching aids, focusing on fostering critical and analytical thinking related to physics and the role of Engineering Physics in technology. The results of this activity showed that the students applied physics principles in the design and functionality of technologies such as communication technology, optical and photonic technology, and computational technology